مدى توافر الخصائص الريادية لدى مديري الفنادق في الساحل السوري دراسة ميدانية - عمار, نضال; عجيل, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The objective of the research is to determine the availability of the Entrepreneurial characteristics (personal, behavioral, administrative) of the hotel managers in the Syrian coast and to come up with a set of proposals that can contribute to the necessity of the hotel managers to adhere to these characteristics. The research was based on the descriptive approach and the survey method. The questionnaire was used as the main source of data and information. The research community consisted of hotel managers (four and five stars) and their assistants in the Syrian coast, where 80 questionnaires were distributed to the managers, 73 of which were fully researched and valid for statistical analysis, with a response rate of 91.25%. The results showed that the leading characteristics in general were very high among hotel managers in the Syrian coast, with a relative importance of (76.36%). As for personal entrepreneurial characteristics, the results showed that they are highly available with a relative importance of (75.07%). (78.08%). In terms of managerial leadership characteristics, the results showed that they are highly available with a relative importance of (77.26%). يهدف البحث إلى تحديد مدى توافر الخصائص الريادية (الشخصية, السلوكية, الإدارية) لدى مديري الفنادق في الساحل السوري, والخروج بمجموعة من المقترحات التي يمكن أن تسهم في ضرورة التزام مديري الفنادق بهذه الخصائص بما ينعكس إيجاباً على جودة الخدمة المقدمة.اعتمد البحث على المنهج الوصفي, وأسلوب المسح, حيث اُستخدمت الاستبانة كمصدر رئيس في الحصول على البيانات والمعلومات. تكون مجتمع البحثمن مديري الفنادق (تصنيف أربع وخمس نجوم) ومعاونيهم في الساحل السوري, حيث تمّ توزيع (80) استبانة على المديرين, وأعيد منها (73) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (91.25%).أظهرت النتائج أنّ الخصائص الريادية بشكل عام تتوافر بدرجة كبيرة لدى مديري الفنادق في الساحل السوري, وبأهمية نسبية بلغت (76.36%), أما بالنسبة للخصائص الريادية الشخصية, فقد أظهرت النتائج أنها تتوافر بدرجة كبيرة وبأهمية نسبية بلغت (75.07%), وبالنسبة للخصائص الريادية السلوكية, فقد أظهرت النتائج أنها تتوافر بدرجة كبيرة وبأهمية نسبية بلغت (78.08%),وبالنسبة للخصائص الريادية الإدارية, فقد أظهرت النتائج أنها تتوافر بدرجة كبيرة وبأهمية نسبية بلغت (77.26%).